A new species of the genus Myiomma (Heteroptera: Miridae: Isometopinae) from the Korean Peninsula - Oh, Minsuk; Kim, Wonwoong; Kim, Wongun; Lee, Seunghwan (Zootaxa, 2025)
In this study, we report the genus Myiomma from the Korean peninsula for the first time, with the description of a new species Myiomma koreana sp. nov. A morphological diagnosis for the genus is provided, accompanied by images of the dorsal habitus and female and male genital structures. Additionally, a key is presented for the identification of the 12 known East Asian species of Myiomma. COI sequence data for the new species are included, along with a neighbor-joining (NJ) tree analysis. This analysis revealed that a COI sequence previously submitted to GenBank, attributed to Myiomma kukai Yasunaga & Hayashi 2002, was a misidentification of our new species.